From Socialization to Participation: Leadership Communication Practices in the Waste Bank Program of the South Tangerang City Environmental Service - lymbarski caesariano; Pudji Muljono; Anna Fatchiya; Siti Amanah (LPPM UBSI, 2026)
Waste management in South Tangerang City faces serious pressure due to limited landfill capacity and low community participation in waste sorting. The waste bank program implemented by the Environmental Agency in partnership with the PERBAS Waste Bank in Kedaung Village is one strategy to reduce waste going to the landfill while empowering the community. This study aims to analyze how leadership communication practices at the institutional and community levels shift residents from passive recipients of socialization to active participants in waste management. A qualitative approach with case studies was used through in-depth interviews, participant observation, and document review. Data were analyzed using the stages of reduction, display, and conclusion. The results show that leadership communication combines the framing of the landfill crisis, narratives of economic and environmental benefits, role models, intensive interpersonal communication, and the innovation of thematic savings schemes close to household needs. These practices form a transformation stage from informative socialization, participatory socialization, collective participation, to co-creation and social entrepreneurship. These findings confirm that the success and sustainability of waste bank programs are determined not only by technical and regulatory aspects, but also by the design of dialogic, adaptive, and multi-layered leadership communication between institutional and community leaders.